An Experimental Study for Quantitative Estimation of Rebar Corrosion in Concrete Using Ground Penetrating Radar. (18th January 2016) - Hasan, Md Istiaque; Yazdani, Nur
Abstract : Corrosion of steel rebar in reinforced concrete is one the most important durability issues in the service life of a structure. In this paper, an investigation is conducted to find out the relationship between the amount of reinforced concrete corrosion and GPR maximum positive amplitude. Accelerated corrosion was simulated in the lab by impressing direct current into steel rebar that was submerged in a 5% salt water solution. The amount of corrosion was varied in the rebars with different levels of mass loss ranging from 0% to 45%. The corroded rebars were then placed into three different oil emulsion tanks having different dielectric properties similar to concrete. The maximum amplitudes from the corroded bars were recorded. A linear relationship between the maximum positive amplitudes and the amount of corrosion in terms of percentage loss of area was observed. It was proposed that the relationship between the GPR maximum amplitude and the amount of corrosion can be used as a basis of a NDE technique of quantitative estimation of corrosion.